Inventory of Vegetable Crude Drug samples housed in Botanical Survey of India, Howrah - Selvam, A.B.D. (Pharmacognosy Reviews)
This paper provides a comprehensive list of about 472 authentic vegetable crude drug samples belonging to about 375 plant species that are housed in the Crude Drug Museum (CDM) of Pharmacognosy Section, Botanical Survey of India (BSI), Howrah. This museum is a repository of raw drug samples or vegetable crude drug samples such as rhizomes, roots, stems, wood, bark, leaves, flowers, fruits, seeds etc. that are commonly used in the Indian Systems of Medicine (ISM). It provides a baseline information on these raw drugs. The various uses of this museum have been highlighted in this paper.
Keywords: Inventory; Vegetable Crude Drugs; Crude Drug Museum; Pharmacognosy Section; Botanical Survey of India